Transition to adulthood and transfer to adult care of adolescents with congenital heart disease: a global consensus statement of the ESC Association of Cardiovascular Nursing and Allied Professions (ACNAP), the ESC Working Group on Adult Congenital Heart Disease (WG ACHD), the Association for European Paediatric and Congenital Cardiology (AEPC), the Pan-African Society of Cardiology (PASCAR), the Asia-Pacific Pediatric Cardiac Society (APPCS), the Inter-American Society of Cardiology (IASC), the Cardiac Society of Australia and New Zealand (CSANZ), the International Society for Adult Congenital Heart Disease (ISACHD), the World Heart Federation (WHF), the European Congenital Heart Disease Organisation (ECHDO), and the Global Alliance for Rheumatic and Congenital Hearts (Global ARCH). (1st July 2021) - Moons, Philip; Bratt, Ewa-Lena; De Backer, Julie; Goossens, Eva; Hornung, Tim; Tutarel, Oktay; Zühlke, Liesl; Araujo, John Jairo; Callus, Edward; Gabriel, Harald; Shahid, Nauman; Sliwa, Karen; et al.
Abstract: The vast majority of children with congenital heart disease (CHD) in high-income countries survive into adulthood. Further, paediatric cardiac services have expanded in middle-income countries. Both evolutions have resulted in an increasing number of CHD survivors. Expert care across the life span is necessitated. In adolescence, patients transition from being a dependent child to an independent adult. They are also advised to transfer from paediatrics to adult care. There is no universal consensus regarding how transitional care should be provided and how the transfer should be organized. This is even more challenging in countries with low resources. This consensus document describes issues and practices of transition and transfer of adolescents with CHD, accounting for different possibilities in high-, middle-, and low-income countries. Transitional care ought to be provided to all adolescents with CHD, taking into consideration the available resources. When reaching adulthood, patients ought to be transferred to adult care facilities/providers capable of managing their needs, and systems have to be in place to make sure that continuity of high-quality care is ensured after leaving paediatric cardiology. Graphical Abstract: